Psychological Recovery of Crime Victims within Contemporary Restorative Justice: An Islamic Legal Perspective - Nur Azisa; Audyna Mayasari Muin; M. Aris Munandar; Muhammad Mutawalli Mukhlis; Aspalella A. Rahman (MILRev: Metro Islamic Law Review, 2025)
This article examines the implementation of Restorative Justice (RJ) in Indonesia, focusing on its effectiveness in addressing victims' psychological recovery. Although RJ has been formally incorporated into national regulations, including Supreme Court Regulation (Perma) No. 1 of 2024 and Prosecutor's Regulation No. 15 of 2020, its practical application often prioritises procedural settlement over substantive victim healing. This study employs normative legal research, combining legislative, case, and conceptual approaches, to analyse RJ's legal framework and the structural barriers to its implementation. The findings identify several persistent challenges: the absence of mandatory psychological assessments, limited involvement of mental health professionals, weak post-mediation monitoring, and socio-cultural factors such as victim blaming and third-party interference. These obstacles undermine voluntariness, reduce effectiveness, and prevent RJ from fulfilling its intended role in safeguarding victims' rights and recovery. This study contributes to the literature by emphasising the urgent need to integrate psychological recovery mechanisms into RJ practices, supported by stronger legal provisions and institutional innovations. Policy recommendations include revising victim protection regulations, incorporating professional psychological support, and establishing specialised recovery centres. In this way, RJ can be repositioned as a mechanism for dispute resolution and a comprehensive, victim-centred framework for achieving substantive justice in Indonesia.